Binder efficiency and CO2 emissivity for cement mortars containing recycling aggregates - Zawal, Daniel; Górski, Krzysztof; Dłużewski, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the application of bi (binder intensity index) and ci (carbon index) coefficients as indicators determining the efficiency of using binders in cement composites in combination with their impact on the environment resulting from CO2 emissions occurring during cement production.
Keywords: binder intensity index; carbon index; cement mortar; recycling aggregate